ROOT DISTRIBUTION OF SWEET CORN (Zea mays) AS AFFECTED BY MANURE TYPES, RATES AND FREQUENCY OF APPLICATIONS - A. Ahmad1; A. Fares; N. V. Hue; M. Safeeq; T. Radovich; F. Abbas3; M. Ibrahim3 (Journal of Animal and Plant Sciences, 2014)
Manure applications can change soil porosity, bulk density, hydraulic conductivity, and nutrient availability, thus affecting root growth and distribution. Information on root distribution is important to developing more efficient irrigation strategies that meets crop water requirement and reduce excess irrigation. Two field experiments were conducted in Hawaii to study the effect of 1) types, 2) rates, and 3) frequency of manure application on root distribution of sweet corn (Zea mays cv. Supersweet 10). The studied variables were roots density, root percentage at 0-15 cm and 16-30 cm depths, and total dry roots per plant. The application of manures and their rates significantly increased the values of all the studied variables except the root percentage at 16-30 cm depth which was highest in the control treatment and was decreased by increasing the application rate. Two-time manure application significantly increased the values of the studied variables at both depths, except for the root percentage at the 16-30 cm depth which decreased under the two time application compared to the one-time application.
Keywords: Root distribution; Corn; Organic matter; Tropical